Studies on biological reduction of chromate by Streptomyces griseus - Poopal, Ashwini C.; Laxman, Ryali Seeta (Journal of Hazardous Materials, 2009)
Chromium is a toxic heavy metal used in various industries and leads to environmental pollution due to improper handling. The most toxic form of chromium Cr(VI) can be converted to less toxic Cr(III) by reduction. Among the actinomycetes tested for chromate reduction, thirteen strains reduced Cr(VI) to Cr(III), of which one strain of Streptomyces griseus (NCIM 2020) was most efficient showing complete reduction within 24h. The organism was able to use a number of carbon sources as electron donors. Sulphate, nitrate, chloride and carbonate had no effect on chromate reduction during growth while cations such as Cd, Ni, Co and Cu were inhibitory to varying degrees. Chromate reduction was associated with the bacterial cells and sonication was the best method of cell breakage to release the enzyme. The enzyme was constitutive and did not require presence of chromate during growth for expression of activity. Chromate reduction with cell free extract (CFE) was observed without added NADH. However, addition of NAD(P)H resulted in 2-3-fold increase in activity. Chromate reductase showed optimum activity at 28 degrees C and pH 7 (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bioreduction; Chromate reductase; Hexavalent chromium; Streptomyces griseus

Subtilase from Beauveria sp.: conformational and functional investigation of unusual stability - Dalal, Sayli A.; More, Snehal V.; Shankar, Shiv; Laxman, Ryali Seeta; Gaikwad, Sushama M. (European Biophysics Journal With Biophysics Letters, 2014)
Retention of total activity of the subtilisin-like serine protease from Beauveria sp. MTCC 5184 (Bprot) in the vicinity of (1) 3 M GdnHCl for 12 h, (2) 50 % methanol and dimethyl sulfoxide each for 24 h, and (3) proteolytic enzymes (trypsin, chymotrypsin, and proteinase K) for 48 h led to expect the enzyme to be a kinetically stable protein. Also, the structure of the protein was stable at pH 2.0. Biophysical characterization and conformational transitions were monitored using steady-state and time-resolved fluorescence, FTIR, and CD spectroscopy. Single tryptophan in the protein exists as two conformers, in hydrophobic and polar environment. The secondary structure of Bprot was stable in 3 M GdnHCl as seen in far-UV CD spectra. The active fraction of Bprot obtained from size-exclusion chromatography in the presence of GdnHCl (1.0-3.0 M) eluted at reduced retention time. The peak area of inactive or denatured protein with the same retention time as that of native protein increased with increasing concentration of denaturant (1.0-4.0 M GdnHCl). However, the kinetics of GdnHCl-induced unfolding as studied from intrinsic fluorescence revealed k (unf) of native protein to be 5.407 x 10(-5) s(-1) and a half-life of 3.56 h. The enzyme is thermodynamically stable in spite of being resistant to the denaturant, which could be due to the effect of GdnHCl imparting rigidity to the active fraction and simultaneously unfolding the partially unfolded protein that exists in equilibrium with the folded active protein. Thermal and pH denaturation of Bprot exhibited interesting structural transitions.
Keywords: Beauveria; Chemical denaturation; Conformational transitions; Serine protease; Subtilase; Thermal denaturation; Thermodynamic stability